The effect of urban development characteristics on the success of TODs - Altheeban, Hamzah (Kansas State University, 2019)
Transit-Oriented Development (TOD) is a set of policies that cities implement around transit stations to incentivize development and create a pedestrian-friendly environment that aims to increase the transit ridership and reduce the use of personal vehicles. Before applying the TOD policies, and in order to ensure their success, the TOD levels will be measured around each station by using some TOD measurements and evaluation techniques. The goal is to get an overview of the TOD levels at each station area and know which areas should be prioritized for the implementation of the TOD policies. The goal of this paper is to enhance this method by identifying which station areas encounter more development (areas with high, mid, or low levels of TOD), and thus, help decision-makers know which areas should be prioritized for the implementation of TOD policies. To do that, we calculated the residential and commercial density, land use diversity, land use mixedness, and economic development in 94 Chicago Transit Authority (CTA) stations for two separate years, 2010 and 2017. After comparing the results, we found out that, although some station areas with low levels of TOD have encountered a noticeable increase in their TOD level, station areas with mid levels of TOD have encountered more change. Thus, we came to a conclusion that station areas with mid levels of TOD should be prioritized in the implementation of TOD policies because they yield in more successful TOD areas in a short time period.
Keywords: TOD index; Transit-Oriented Development; Chicago